Aspects of the characteristics of financial reports from governments through organizational commitment - Nurul Fuada; Asbi Amin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2021)
The purpose of this research is to demonstrate that the capacity of the financial apparatus and the clarity of the objectives of the budget have an impact on the characteristics of government financial reports and the clarity of the objectives of the budget on the characteristics of government financial statements. Organizational commitment is capable of moderating the relationship between the capacity of the financial apparatus and the clarity of the objectives of the budget with the characteristics of the financial reports of the government. This is a quantitative study of primary data. The population in this study was responsible for making the financial reports of the Makassar City Regional Apparatus Organization using a purposeful sampling technique by the head of administration and accounting staff, so that the sample was fifty-four people. A questionnaire survey collected data and tested it through Partial Least Square (PLS) analysis. The results demonstrate that the capacity of the financial apparatus and the clarity of the budget objectives have a significant impact on the characteristics of government financial reports. The organizational commitment, however, was unable to moderate the relationship between the capacity of the financial apparatus and the clarity of the budgetary objectives with regard to the characteristics of government financial reporting.